Hidrostratigrafi Akuifer sebagai Geoindikator Genesis Bentuk Lahan di Wilayah Kepesisiran Kabupaten Kulonprogo, Daerah Istimewa Yogyakarta - Santosa, Langgeng Wahyu (Forum Geografi, 2012)
Purpose of this research is to study on aquifer hydrostratigraphy that can be a geo-indicator of geomorphological processes on the past, that describe of landform genetic in the research area. The research method is survey. The framework of analysis in this research is landform genetic. The results of the research indicate that: (1) "the forming of aquifer hydrostratigraphy in the research area is controlled by some of main processes in geomorphology, that show of landform genetic specifically". The research area consists of 3 aquifer hydrostratigraphy systems, each of the aquifer system has the typical characteristic, showed by system and pattern of material stratigraphy in the aquifer and variation of groundwater characteristic in the unconfined aquifer. (2) "spatiotemporally, landform genetic in the research area influences on the forming of aquifer hydrostratigraphy in the 3 phases, i.e. the first stage at the end of the Tertiary epoch (end of Pliocene era), second stage at the Quaternary epoch (as long as the Pleistocene period), and third stage at the Holocene era". The genesis and chronology of landform forming in the 3 phases above influence on the forming of system and pattern of aquifer hydrostratigraphy in the research area.